STREETLIGHT MONITORING SYSTEM USING A WIRELESS SENSOR NETWORK - LIEW, ZHI HONG (IRC, 2019)
This project presents a study of wireless sensor network (WSN) system for the energy- efficient street lighting monitoring system. The conventional street lighting system consumes high electrical energy and does not provides real-time monitoring. In this project, a street lighting monitoring system using wireless sensor network is proposed in order to provide the features such as real-time monitoring. The multi-hop transmission is implemented in the proposed street lighting monitoring system using the ZigBee technology in order to conserve transmission energy. The existing technologies such as LED light source and sensors are integrated into the street lighting monitoring system. Besides that, the function of sensors such as LDR sensor and PIR sensor are validated and evaluated in this project. There are several experiments conducted to study the performance of XBee which include the maximum transmission range, received signal strength indicator (RSSI) and packet ratio versus distance as well as the transmission time of receive and transmit single packet. The findings show that the multi-hop communication is capable of extending the distance of the transmission between the receiver and transmitter. The prototype for the proposed street lighting monitoring system is designed to demonstrate the working concept of the system. The prototype contains three different streetlights which are Streetlight Transmitter, Streetlight Intermediate and Streetlight Receiver.